Measuring quality in planning. Managing the performance process. - Carmona, Matthew; Sieh, Louie (Spon, 2004)
Wie lässt sich die Qualität von Planungsergebnissen messen? Zunächst werden die Begriffe Qualität, Planungsqualität, Planungsziel, Effizienz geklärt sowie die Darstellung des "Modernising Local Government", der englischen Variante des weltweiten New Public Managements, um dann einzelne Elemente der Effizienz- oder Qualitätsmessung näher zu bestimmen. Der zweite Teil nimmt nach einem erneuten Blick auf das theoretische Rahmenwerk von Qualität, Governance, Effizienz und Planung die aktuelle Planungspraxis ins Visier, vor allem die Befragung von 416 Planungsinstanzen auf regionaler oder lokaler Ebene im "National survey of local authorities" und vergleicht sie mit internationalen Untersuchungen aus anderen europäischen Ländern, Neuseelands und den USA. Schließlich wird auf der Basis von zahlreichen Fallstudien die Innovation der englischen Planungspraxis untersucht und ein eigenes Modell für die Qualitätsmessung von Planung entwickelt.

How can a non-distortionary, objective and comprehensive system be developed in order to measure the quality of planning? This is an important question if the situation is to be avoided whereby those aspects of the planning service which are difficult to measure are devalued, simply because they do not lend themselves to easy measurement. Examining this conundrum provided the basis for the research project on which this book is based. These questions have been recognised by governments across the world and are beginning to be addressed in policy developments and in management practice. However, the fundamentals of performance measurement in planning are by no means well - understood, let alone practised, leading to the situation whereby much performance measurement is highly distortionary and can act against the drive to deliver better quality planning. It is the purpose of this book to address the complexities, and - as far as possible - to cut through the tangled web of thinking that has dogged performance (or quality) measurement in planning, and in the public sector at large. Through research that draws extensively from experience in the UK, but also from practice and theory from around the world, this book argues the case for a holistic approach to quality measurement that addresses equally the three key dimensions of planning quality: product, service and organisational quality.
Keywords: Stadtplanung; Kommunalplanung; Planungsprozess; Planungspraxis; Planungstheorie; Gemeinde; Messung; Bewertung; Erfolgskontrolle; Effektivität; Vergleichsuntersuchung; Fallstudie; Qualität; Qualitätsmanagement; Nachhaltigkeit; Modernisierung; Evaluation; Local Governance